Simulator Perbandingan Data Rate Modulasi QPSK dan 16 QAM Sistem WCDMA (Wide Code Division Multiple Access) dan HSDPA (High Speed Downlink Packet Access) - Herdianna Kusuma w (Politeknik Negeri Malang, 2015)
HSDPA (High Speed Downlink Packet Access) is the upgrade performance data packets extraordinary against WCDMA thus producing top speed 14,4 Mbps. One of the goals the creation of HSDPA is as an improvement over previous technologies. The expected improvement of HSDPA technology increasing the data rate is capable of exceeding data rate in order to WCDMA customer satisfaction in accessing multimedia content such as streaming video and data at high speed. Data Rate is the maximum data rate that can be accepted by the UE (User Equipment) in ideal conditions. One of the factors that affect the data rate is modulation scheme used by each of the technologies. QPSK modulation is used in WCDMA system and adaptive modulation (QPSK and 16QAM) is used in HSDPA system.In the research the results obtained by selection of symbol rate of 480 kbps bit rate will yield 960 kbps while the selection symbol rate is 960 kbps will produce 1920 kbps bit rate using modulation QPSK modulation. As for 16QAM modulation, symbol rate of 480 kbps produces 1920 kbps and symbol rate is 960 kbps bit rate produces 3840 kbps. Of the trial results, the more number of bits sent then the higher data rate that can be accepted by the UE (user equipment).